1993
DOI: 10.1002/j.1460-2075.1993.tb05658.x
|View full text |Cite
|
Sign up to set email alerts
|

p60v-src causes tyrosine phosphorylation and inactivation of the N-cadherin-catenin cell adhesion system.

Abstract: Transformation of chick embryonic fibroblasts with Rous sarcoma virus strongly suppresses N‐cadherin‐mediated cell‐cell adhesion, without inhibiting its expression. This suppression is correlated with tyrosine phosphorylation of N‐cadherin and catenins, the cadherin‐associated proteins, which are known to regulate cadherin function. Experiments with non‐myristylation and temperature‐sensitive mutants of RSV and with herbimycin A, a potent inhibitor of tyrosine kinases, suggest that both the suppression of cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
283
4

Year Published

1996
1996
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 391 publications
(298 citation statements)
references
References 47 publications
11
283
4
Order By: Relevance
“…In the huiman gastric cancer cell line, HSC-39, mutation in the f-catenin gene that resulted in complete abolishment of E-cadherin-dependent cell-cell adhesion was observed, and transfection of the f-ctenin gene in the cells fully recovered the cell-cell adhesion (Kawanishi et al, 1995). We have previously reported (Matsuyoshi et al, 1992;Hamaguchi et al, 1993a) that cadherin dependent cell-cell adhesion was strongly erturbed upon tyrosine phosphorylation of f-catenin in RSV-transformed cells where cadherins and catenins were expressed and formed complexes as normal cells. Another pTyr-containing protein, pl20, was also identified as a major pTyr-containing protein in RSVtransformed cells whose phosphorylation closely correlated with cell transformation (Reynolds et al, 1989).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the huiman gastric cancer cell line, HSC-39, mutation in the f-catenin gene that resulted in complete abolishment of E-cadherin-dependent cell-cell adhesion was observed, and transfection of the f-ctenin gene in the cells fully recovered the cell-cell adhesion (Kawanishi et al, 1995). We have previously reported (Matsuyoshi et al, 1992;Hamaguchi et al, 1993a) that cadherin dependent cell-cell adhesion was strongly erturbed upon tyrosine phosphorylation of f-catenin in RSV-transformed cells where cadherins and catenins were expressed and formed complexes as normal cells. Another pTyr-containing protein, pl20, was also identified as a major pTyr-containing protein in RSVtransformed cells whose phosphorylation closely correlated with cell transformation (Reynolds et al, 1989).…”
Section: Discussionmentioning
confidence: 98%
“…These proteins were known as major components of the cell adhesion system and their tyrosine phosphorylation showed good correlation with transforming activity of v-Src kinase (Schaller et al, 1992;Illic et al, 1995;Matsuyoshi et al, 1992;Hamaguchi et al, 1988Hamaguchi et al, , 1993aIllic et al, 1995;Reynolds et al, 1989Reynolds et al, , 1992. Thus, tyrosine phosphorylation of these proteins may perturb cell-cell adhesion and activate tumour cell movement, invasion and metastasis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that multiple kinases and phosphatases regulate cadherin function, possibly each playing a role in a specific tissue and at a specific time during development. Overexpression of the nonreceptor tyrosine kinases Src (Matsuyoshi et al, 1992;Hamaguchi et al, 1993;Behrens et al, 1993), and Fer (Rosato et al, 1998) has been demonstrated to increase tyrosine phosphorylation of ␤-catenin (and p120 ctn ). Furthermore, a dominant-negative Src that interferes with function, or a Src-specific tyrosine kinase inhibitor induce cell-cell adhesion (Owens et al, 2000), further suggesting that Src plays an in vivo role in regulating the phosphotyrosine content of ␤-catenin and that suppression of tyrosine phosphorylation of ␤-catenin promotes formation of cadherin-mediated adhesions.…”
Section: Destabilizing Adhesions: Altering the Balance Between Phosphmentioning
confidence: 99%
“…By use of mutant src genes, several cellular proteins have been described as transformation-relevant substrates of v-Src kinase. These include; b-catenin (Hamaguchi et al, 1993a); glycoproteins of 95 kDa and 130 kDa (Hamaguchi et al, 1990;Kozuma et al, 1990); connexin-43 (Crow et al, 1992;Kanemitsu et al, 1997); 120-kDa protein (Linder and Burr, 1988). Thus, mutant src genes have been utilized as an e cient tool to characterize substrate proteins.…”
Section: Introductionmentioning
confidence: 99%